Partial Ground-Inserted H-shaped Antenna for Beyond 5G Applications - Dwivedi S. (My University, 2025)
Inserted H-shaped antenna with partial ground has been presented here with three major designs and their comparison at terahertz frequency for beyond 5G applications. This new era of beyond 5G is useful to connect most of the devices and create a proper balance between systems and users as per demand of technology. Antenna design is proposed with normal rectangular patch and two more modifications have been done in same patch and it is simulated with the help of CST microwave studio for its important parameters such as bandwidth and gain. For the three structures first design, second design and third design bandwidth is 100 GHz, 250 GHz and 400 GHz with gain 13.5 dBi, 14.4 dBi and 14.8 dBi, respectively. A simple PEC material as a radiating element and polyamide as substrate have been taken. Partial ground has been taken with microstrip line feedline. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.